(untitled) (Progressive Agriculture, 2013)
The merit of Red Chittagong cows-a promising indigenous cattle genetic resource of Bangladesh was evaluated by using test day milk yield records of total 41 individuals. The data were collected from the Nucleus Herd of Red Chittagong (RC) cattle maintained at Bangladesh Agricultural University, Mymensingh from June, 2007 to October, 2008 under supervised animal recording system along with the previously recorded data from 2005 was also taken into consideration. Data were then analyzed for evaluating the cows based on lactation yield and average daily milk yield. Average lactation yield and daily milk yield were 453.86 ± 59.61 and 1.99 ± 0.14 kg, respectively. The highest lactation yield (538.04 kg) and daily milk yield (2.3 kg) was found in 4th and 5th lactation, respectively. The most probable producing ability (MPPA) of RC cows was calculated by using the test day records and then the animals were ranked on the basis of their MPPA value. For MPPA calculation two methods were followed; cows repeated lactation performance (MPPA1) and within lactation repeated test day records and averaged (MPPA2). The highest MPPA for lactation yield was shown by the cow no. 36 (645.61 kg) and the highest MPPA1 and MPPA2 for daily milk yield were 2.83 and 3.46 kg, respectively for cow no. 03. The result of this study suggests that test-day yields may well be used for genetic evaluation of cows to make recurrent selection decision in cattle breeding programs. DOI: http://dx.doi.org/10.3329/pa.v19i2.16950 Progress. Agric. 19(2): 101 - 109, 2008